Kekuatan Hukum Akta Keterangan Hak Waris Yang Dibuat Notaris Bagi Warga Negara Indonesia Asli - Hambyah Agung Sutrisno (Faculty of Law Universitas Islam Indonesia, 2022)
Provisions regarding inheritance certificates used to proving someone as heirs and the institutions that make them are still based on a certain ethnicity. The provisions of Article 111 paragraph (1) of the Regulation of the Minister of Agrarian Affairs/Head of BPN Number 3 of 1997 on Provisions for the Implementation of Government Regulation Number 24 of 1997 on Land Registration states that Indonesian Citizens are Indigenous, a certificate of inheritance is sufficient to be made by the heirs and ratified by the Chief of Village and confirmed by the Chief of District. However, it was later found that the practice of a notary making a certificate of inheritance rights for native Indonesian citizens was used as evidence for managing inheritance rights. In this study, problems emerged related to the legal basis for the strength of the Deed of Inheritance Rights made by a Notary for Indigenous Indonesian Citizens and the legal force of the deed made by a Notary for Indigenous Indonesian Citizens. Based on these two problems, this research was conducted using library research and field research, so this research is an empirical juridical research. After conducting research, the results obtained are in the form of a legal basis for the strength of the Deed of Inheritance Declaration made by a Notary for Indigenous Indonesian Citizens, namely the Regulation of the State Minister for Agrarian Affairs/Head of BPN Number 3 of 1997 on Implementation of Government Regulation Number 24 of 1997 on Land Registration and Letters from the Department of Home Affairs. Directorate General of Agrarian Affairs Directorate of Land Registration Number Dpt/12/63/12/69 on Certificates of Inheritance and Proof of Citizenship by setting aside provisions regarding the classification of the population based on certain groups, races and ethnicities because it is against the above regulations based on the principle of lex superior derogat legi inferiori and although these regulations are still in effect today, the provisions in these regulations are not enforced in the process of inheritance in banking.Key Word: Proof of Heirs, Certificate of Inheritance, Deed of Inheritance Information AbstrakKetentuan mengenai surat keterangan waris yang digunakan untuk pembuktian sebagai ahli waris dan institusi yang membuatnya masih didasarkan pada etnis tertentu. Ketentuan Pasal 111 ayat (1) Peraturan Menteri Negara Agraria/Kepala BPN Nomor 3 Tahun 1997 tentang Ketentuan Pelaksanaan Peraturan Pemerintah Nomor 24 tahun 1997 tentang Pendaftaran Tanah disebutkan Warga Negara Indonesia penduduk Asli, surat keterangan waris cukup dibuat oleh para ahli waris dan disahkan oleh Lurah dan dikuatkan oleh Camat. Namun kemudian ditemukan praktek Notaris membuat Akta Keterangan Hak Waris bagi WNI penduduk asli dan dipergunakan sebagai alat bukti pengurusan hak waris. Pada penelitian ini kemudian muncul permasalahan terkait dengan dasar hukum kekuatan Akta Keterangan Hak Waris yang dibuat oleh Notaris bagi WNI Asli serta kekuatan hukum akta tersebut yang dibuat oleh Notaris bagi WNI Asli. Berdasarkan kedua permasalahan tersebut, penelitian ini dilakukan dengan penelitian kepustakaan dan penelitian lapangan, sehingga penelitian ini merupakan penelitian yuridis empiris. Setelah dilakukan penelitian, kemudian didapatkan hasil berupa dasar hukum kekuatan Akta Keterangan Hak Waris yang dibuat oleh Notaris bagi WNI Asli adalah Peraturan Menteri Negara Agraria/Kepala BPN Nomor 3 Tahun 1997 tentang Pelaksanaan Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah dan Surat Departemen Dalam Negeri Direktorat Jenderal Agraria Direktorat Pendaftaran Tanah Nomor Dpt/12/63/12/69 tentang Surat Keterangan Warisan dan Pembuktian Kewarganegaraan dengan mengesampingkan ketentuan tentang penggolongan penduduk berdasarkan golongan, ras dan etnis tertentu karena bertentangan dengan peraturan di atasnya berdasarkan asas lex superior derogat legi inferiori dan meskipun peraturan tersebut masih diberlakukan sampai dengan saat ini, akan tetapi pengaturan dalam peraturan tersebut tidak diberlakukan dalam proses turun waris di perbankan.Kata-kata Kunci: Pembuktian Ahli Waris, Surat Keterangan Waris, Akta Keterangan Hak Waris